Investigation of Cultural Elements in Short Stories Collection Kenangan di Indonesia BIPA Development Learning Material - Rahmi Yulia Ningsih; Kristianus Oktriono; Chandra Kurniawan Wiharja (Universitas Brawijaya, 2019)
This research is aimed to identify elements of culture within short stories collection “Kenangan di Indonesia” written by BIPA BINUS 2019 students. The research method used in this study is qualitative method with content analysis techniques. The source of the research is 17 short stories compositions in the book ”Kenangan di Indonesia” by BIPA BINUS 2019 students. The study results demonstrate that (a) element of culture in the form of artifacts found in “Kenangan di Indonesia” compositions are tourist attractions, historic sites, and Indonesian food; (b) element of culture in the form of values found in “Kenangan di Indonesia” are value of habits such as speech habits, greeting habits, bargaining habits, habits of kissing hands with older people, habits of helping strangers, and cooperating to achieve something; (c) element of culture in the form of ideas contained in “Kenangan di Indonesia” are Balinese culture, belief in the supernatural, and belief in certain Indonesian food. These cultural elements can be utilized in developing BIPA teaching materials and can be integrated in teaching language skills and grammar for BIPA students.